2018
DOI: 10.3389/fneur.2018.00630
|View full text |Cite
|
Sign up to set email alerts
|

Electromyography Assessment During Gait in a Robotic Exoskeleton for Acute Stroke

Abstract: Background: Robotic exoskeleton (RE) based gait training involves repetitive task-oriented movements and weight shifts to promote functional recovery. To effectively understand the neuromuscular alterations occurring due to hemiplegia as well as due to the utilization of RE in acute stroke, there is a need for electromyography (EMG) techniques that not only quantify the intensity of muscle activations but also quantify and compare activation timings in different gait training environments.Purpose: To examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 26 publications
2
53
0
Order By: Relevance
“…Stroke etiology was reported in 92 cases: 72 of which were ischemic in origin, 18 were hemorrhagic, and two were ischemic/hemorrhagic. Six studies did not provide information related to stroke type (Ping et al, 2013 ; He et al, 2014 ; Androwis et al, 2018 ; Sloot et al, 2018 ). The time from stroke to study participation was reported for 98 patients, with the majority ( N = 57) recruited in the chronic phase of stroke.…”
Section: Resultsmentioning
confidence: 99%
“…Stroke etiology was reported in 92 cases: 72 of which were ischemic in origin, 18 were hemorrhagic, and two were ischemic/hemorrhagic. Six studies did not provide information related to stroke type (Ping et al, 2013 ; He et al, 2014 ; Androwis et al, 2018 ; Sloot et al, 2018 ). The time from stroke to study participation was reported for 98 patients, with the majority ( N = 57) recruited in the chronic phase of stroke.…”
Section: Resultsmentioning
confidence: 99%
“…The area under the sEMG envelopes were calculated by numerical integration, which is called integral electromyogram (IEMG). IEMG is positively related with muscle strength and activity, which is a practical index for muscle function assessment [19,40] . Fig.5 B compares the IEMG of measured bilateral muscles between circumstances with or without exoskeleton assistance.…”
Section: Semgmentioning
confidence: 99%
“…Through the analysis of the above clinical researches, it is found that the rehabilitation effect of exoskeleton robot varies in different stages of stroke and different joints of limbs [13][14][15][16] , the key to improving its clinical effect lies in the mechanism design and software control [17][18][19][20] , and there is no mature research paradigm of gait training assisted by exoskeleton robot for stroke patients [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…• to support diagnosis (2,23) • to design complex surgical interventions [e.g., multilevel surgery of hemiplegic children (24,25)] • to design personalized rehabilitation protocols and objectively prove their effectiveness (e.g., outcome evaluation of a proprioceptive training in MS patients), including new rehabilitation trends exploiting exoskeletons, e.g., in acute stroke patients (26), neurorehabilitation with Functional Electrical Stimulation (FES) (27), and any other system providing biofeedback based on myoelectric control (28)(29)(30)(31) • to support clinical decision (e.g., appropriate candidate selection for botulin toxin injection and choice of the target muscles (32), evidence-based choice of the type of joint prosthesis to implant (15) • for therapy evaluation (e.g., to assess the effects of levodopa, or Deep Brain Stimulation on the muscle activation and muscle synergies of PD patients) (33)(34)(35) • for the production of quantitative reports to optimize patient's follow-up or to conduct longitudinal studies (16) • to evaluate muscle fatigue (e.g., in ergonomics and sports) (36-39) • to support forensic medicine with objective outcomes (e.g., to help medical insurance companies estimating a patient's risk, establishing adequate insurance compensations, unmasking simulators and avoiding frauds) (40,41).…”
Section: Introductionmentioning
confidence: 99%